2021
DOI: 10.1186/s13018-021-02856-x
|View full text |Cite
|
Sign up to set email alerts
|

Trapeziectomy for basal thumb osteoarthritis does not increase the risk of developing wrist osteoarthritis in the long term

Abstract: Background Symptomatic osteoarthritis of the basal joint of the thumb (trapeziometacarpal joint) is a common disabling condition mainly affecting women. It is frequently treated with complete removal of the trapezium with or without soft-tissue interposition. There is limited evidence about whether removal of the trapezium affects stability of the wrist joint and increases the risk of developing wrist osteoarthritis. The aim of this study was to evaluate the long-term prevalence of OA in wrists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…118,120 Though radiographic evidence of carpal collapse and degenerative change can be seen following trapeziectomy, functional outcomes are not necessarily correlated. [121][122][123][124]…”
Section: Trapeziummentioning
confidence: 99%
“…118,120 Though radiographic evidence of carpal collapse and degenerative change can be seen following trapeziectomy, functional outcomes are not necessarily correlated. [121][122][123][124]…”
Section: Trapeziummentioning
confidence: 99%
“…In a recent study, Swedish researchers found that trapeziectomy does not increase the risk of developing wrist osteoarthritis (OA) in the long term. (See Brogren et al, 2021. )…”
mentioning
confidence: 99%